Economic Feasibility Study on The Development of Irrigation Channels - Zakia, Zakia; Safriani, Meylis; Radianica, Nessa; Ikhwali, M Faisi (Malikussaleh University, Aceh, Indonesia, 2022)
Indonesia is an agricultural country where the livelihood of the majority of the population is farming. Geographically, Indonesia is an archipelagic country that has enormous natural potential, both in the marine and agricultural fields. The agricultural sector is a sector that has an important role in improving the welfare of the entire population of Indonesia. Rice fields in Blang Beurandang Village still rely on irrigation from using rainwater to meet irrigation water needs. To increase rice yields, an irrigation network is needed that can flow water to the rice fields. It is necessary to conduct a feasibility study on the irrigation to be built so that it can be calculated from an economic point of view whether the project is feasible or not. This feasibility study is equipped with an analysis using the first method; Net Present Value (NPV), the second is the Benefit Cost Ratio (BCR) analysis, the third is the Internal Rate of Return (IRR), and the fourth is the Break Event Point (BEP). The results of this study are the value of the investment cost of the construction project or the initial capital of the irrigation canal which is IDR. 2,088,058,500, and the value of the operational and maintenance costs is IDR. 9,578,250 per year. The results obtained that NPV was IDR. 30,614,330, BCR was 1.01%, IRR was 5.88% 5% and BEP occurred in the 22nd year and the 7th month. Based on the calculation results obtained from these four methods, it shows that the irrigation channel construction project has met the eligibility requirements and the project can be implemented or built. This means that the construction of irrigation networks in the village is feasible.